Pelatihan Penyusunan Menu Dan Pengolahan Pangan Berbasis Kearifan Lokal Pada Ibu Menyusui Dalam Pencegahan Stunting - Mitra, Mitra; Nurlisis, Nurlisis; Rany, Novita (Universitas Islam Negeri Sumatera Utara, 2023)
The achievement of exclusive breastfeeding in the working area of the Karya Wanita Community Health Centre in Pekanbaru City has yet to reach its target. Community Health Centre Karya Wanita is one of the focus locations for reducing stunting prevalence in Pekanbaru City, Riau Province. Lack of breast milk production is the cause of mothers not breastfeeding their babies. This community service aims to increase mothers' knowledge and skills in preparing menus and processing local wisdom-based food ingredients to prevent stunting in toddlers. The community service method was carried out using lectures and discussions, food processing practices, counselling and measuring the nutritional status of toddlers. The training participants were 12 breastfeeding mothers in the Working Area of Community Health Centre Karya Wanita Pekanbaru City. The training was held at Integrated Health Post Petak Bersilang RW 16 Limbungan Baru Village, Rumbai Pesisir Sub-district, Pekanbaru City, on 21 August 2023. The community service procedure starts with preparation, implementation, and evaluation. Preparation is done through coordination with the health centre and recording breastfeeding mothers in the Karya Wanita Community Health Centre Working Area. Evaluation was carried out through assessment of pre-test and post-test answers to mothers' knowledge and attitudes. Data analysis was presented univariately through a frequency distribution table of mothers' knowledge and attitudes. The service results showed an increase in the value of knowledge and attitudes of mothers before and after training. Mothers are expected to implement the material provided to increase breast milk production and prevent toddler stunting.